Disruption of the TWEAK/Fn14 pathway prevents 5-fluorouracil-induced diarrhea in mice - Sezaki, Takuhito (World J Gastroenterol, 2017)
AIM: To clarify the roles of TWEAK and its receptor Fn14 in 5-fluorouracil (5-FU)-induced diarrhea. METHODS: Diarrhea was induced in wild-type (WT), Fn14 knockout (KO), and IL-13 receptor (IL-13R)α1 KO BALB/c mice using a single injection of 5-FU. Histological analysis, cytokine analysis, and flow cytometry was performed on ileal tissues and cells. Murine colon carcinoma-bearing mice were co-treated with an anti-TWEAK antibody and 5-FU. Embryonic fibroblast response to cytokines was also analyzed. RESULTS: 5-FU induced high Fn14 expression in epithelial cells. The severity of 5-FU-induced diarrhea was lower in Fn14 KO mice compared with WT mice. Administration of anti-TWEAK antibody reduced 5-FU-induced diarrhea without affecting the antitumor effects of 5-FU in vivo. 5-FU-induced expression of IL-13, IL-17A, TNF-α, and IFN-γ in the ileum was Fn14 dependent. The severity of 5-FU-induced diarrhea was lower in IL-13Rα1 KO mice, indicating major role for IL-13 signaling via IL-13Rα1 in pathogenesis. We found that IL-13Rα2, an IL-13 neutralizing/cell protective receptor, was strongly induced by IL-33 in vitro and in vivo. IL-13Rα2 was upregulated in the ileum of 5-FU-treated Fn14 KO mice. Thus, the deletion of Fn14 upregulated IL-13Rα2 expression, which reduced IL-13 expression and activity. CONCLUSION: Disruption of the TWEAK/Fn14 pathway affects several interconnected pathways, including those associated with IL-13, IL-33, and IL-13Rα2, to attenuate 5-FU-induced intestinal side effects.